Astrology as Religion: Theory and Practice - Laishley, Lilan (Journal for the study of religion, nature and culture, 2007)
Astrology can be understood as religious in both its principles and practices. A standard definition of religion is used to track astrology’s theoretical, practical, and sociological components. Theoretically, astrology’s Western foundations come from Plato and his story of creation, Timaeus. In establishing a relationship between the larger world of God (macrocosm) and the smaller world of humankind (microcosm), astrology illustrates the Greek concept of an interconnected cosmos. The practice of astrology as a nature religion arises from astrology’s literal, metaphorical, symbolic, and perceptual links to nature. The intersection of time and place at each person’s birth establishes an ‘axis of placement’ connecting each person to the natural world. Astrological practices include tracking the movement of the sun, moon, and planets; ritual participation in the cycles of nature; and honoring nature as sacred. Sociologically, astrology has an amorphous organizational structure, lack of a clear doctrine, and few identifiable institutional partnerships.